PEMBUATAN MI INSTAN DARI TEPUNG JAGUNG LOKAL RIAU DENGAN PENAMBAHAN BROKOLI (Brassica oleracea L.,) - Thofik Arifin; Akhyar Ali; Faizah Hamzah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Instant noodles is favorite food in Indonesia. Instant noodles generally made from wheat flour, which is not Indonesian agricultural product. Diversification was needed to solve this problem. Corn flour is potential resource to develop. Instan noodles generally low nutrient, then need to addition other food matter like broccoli have a lot of calcium. The purpose of this study was to obtain the ratio of corn flour and broccoli that meet the quality of instant noodles on SNI 01-3551-2000. This research was carried out experimentally using completely randomized design (CRD) with five treatments and four replications. The treatments in this study include JB1 (ratio corn flour and broccoli 11:0), JB2 (ratio corn flour and broccoli 10:1), JB3 (ratio corn flour and broccoli 9:2), JB4 (ratio corn flour and broccoli 8:3), and JB5 (ratio corn flour and broccoli 7:4). The data obtained were treated by the analysis of variance (ANOVA) and followed by a test using Duncan New Multiple Range Test (DNMRT) at the level of 5%. The best instant noodles of this study was JB3 (ratio corn flour and broccoli 9:2). The best instant noodles results showed moisture content 6.62%, protein 5.86%, acid number 0.51%, calcium 13.56 mg/g, rehydration time 5.72 minutes and intactness 93.77% with description color was yellow, corn flavour, corn taste, hard texture and the panelists expressed the impression like.Keywords : instant noodles, corn flour and broccoli.